Bilingual Education : Southeast Asian Perspectives - Lin, Angel, 1962- (Book collections on Project MUSE., 2009)
There is an urgent need to critically integrate and review the international research literature with a view to informing public debates and policy making regarding the medium of instruction in Hong Kong and other Southeast Asian contexts. This book aims to meet this need.